Working memory enhancement during early childhood based on the utilization of interactive gesture game-based learning technique - D. Lakshmi; Ponnusamy Ponnusamy (Institute of Advanced Engineering and Science, 2021)
The use of human computer interaction is considered to be the most culturally and socially meritorious for the learning and playing activities of children. In this paper, a human interaction recognition system (HIRS) that includes gesture game-based learning is investigated for identifying its suitability and applicability in stimulation of working memory and primitive mathematical skills among the children in the early childhood period that ranges from 5 and 8 years. In the proposed human interaction recognition system, the hand gestures are facilitated by the user for the objective of controlling the computer system based on the information extracted from the user gestures.This proposed research was implemented in three phases using a quasi-experimental design that in turn incorporates pre-test and post-test for investigating the behavior of experimental and control group considered from the respondents. In the first phase, the initial evaluation of the learner’s skill is achieved. The second phase used the developed technology in order to identify diversified parameters in different dimensions that contribute towards the assessment of working memory and primitive mathematical capabilities. Finally, the third phase is responsible for actual evaluation. In the phases of evaluation, four working memory tests such as forward Corsi Blocking-Tapping test, backward Corsi Blocking-Tapping test, Forward Digit Span test and backwardDigit Span test was conducted. In addition, the evaluation was also conducted for assessing primitive mathematical skill of children using TEDI-MATH. The results confirmed that Gesture Interactive Game-Based Learning (GIGL) used by the children exhibited a predominant improvement in the working memory and primitive mathematical skills on par with their usual school activities.